Career Growth Opportunities and Their Influence on Retention of Gen Z Employees in the IT Sector (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In today’s competitive IT sector, retaining Gen Z employees — individuals born between 1997 and 2012 — has become increasingly challenging. This study investigates the influence of career growth opportunities on the retention of Gen Z employees in IT organizations. A quantitative research design was employed, surveying 150 Gen Z IT professionals through a structured questionnaire. Data analysis, including Pearson correlation, mean score analysis, and Chi-square testing, revealed a strong positive relationship between perceived career growth opportunities and retention intention. Results show that access to mentorship, skill development programs, and clear promotion pathways significantly enhance Gen Z employees' commitment to their organizations. The findings emphasize the strategic importance of investing in employee career development to reduce attrition rates and build a loyal, motivated workforce. This study fills an important research gap by offering targeted insights into effective retention strategies for Gen Z talent in the rapidly evolving IT industry.